2020
DOI: 10.1111/sapm.12349
|View full text |Cite
|
Sign up to set email alerts
|

High‐order exceptional points and enhanced sensing in subwavelength resonator arrays

Abstract: Systems exhibiting degeneracies known as exceptional points have remarkable properties with powerful applications, particularly in sensor design. These degeneracies are formed when eigenstates coincide, and the remarkable effects are exaggerated by increasing the order of the exceptional point (i.e., the number of coincident eigenstates). In this work, we use asymptotic techniques to study scriptPT‐symmetric arrays of many subwavelength resonators and search for high‐order asymptotic exceptional points. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Our results in this paper can be of immense importance for the mathematical foundation of other non-reciprocal guiding phenomena such as the valley Hall effect [16,23,25,26,32,48] and the skin effect [33,44,49]. The valley Hall effect may occur in truncated honeycomb lattices of time-modulated subwavelength resonators by opening non-reciprocal band gaps at Dirac points [6,12] while the skin effect may be obtained by opening non-reciprocal band gaps at exceptional points associated with the unmodulated structure [3,4,14]. These two challenging topics will be the subject of forthcoming publications.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our results in this paper can be of immense importance for the mathematical foundation of other non-reciprocal guiding phenomena such as the valley Hall effect [16,23,25,26,32,48] and the skin effect [33,44,49]. The valley Hall effect may occur in truncated honeycomb lattices of time-modulated subwavelength resonators by opening non-reciprocal band gaps at Dirac points [6,12] while the skin effect may be obtained by opening non-reciprocal band gaps at exceptional points associated with the unmodulated structure [3,4,14]. These two challenging topics will be the subject of forthcoming publications.…”
Section: Discussionmentioning
confidence: 76%
“…Here, the subwavelength nature stems from a high material contrast between the constituting materials of the structure. Such structures can be used to achieve a variety of effects [1,[3][4][5][6][7][8][9]12]. Of particular importance for us are systems of time dependent high-contrast resonators.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7: We study the effects of removing resonators from a cochlea-inspired rainbow sensor. (a) The rainbow sensor with a single resonator removed, denoted D (5) . (b) The rainbow sensor with multiple resonators removed, denoted D (2,5,8,9) .…”
Section: Higher-order Resultsmentioning
confidence: 99%
“…The readers are referred to [7,11,12,[18][19][20][21][22][23][24][25]29] for the detailed investigation of different resonant phenomena for several typical subwavelength structures. Other related mathematical studies on the subwavelength resonant wave scattering and their applications can be found in [2][3][4][5] and references therein. In this work, we consider the three-dimensional problem and present quantitative analysis of scattering resonances for the acoustic wave scattering by a subwavelength hole embedded in a sound hard slab.…”
Section: Introductionmentioning
confidence: 99%